Assessment on Internal Audit Capability Level in a Public Sector Organisation - Hasnah, Haron; Ishak, Ismail; Yuvaraj, Ganesan; Fathyah, Hashim; Aireen Mak, Siew Fern (The Institute of Internal Auditors Malaysia, 2016)
The Institute of Internal Auditor (IIA) states that the internal auditing plays an independent, objective assurance and consulting role. They are intended to add value by playing its auditing role in assisting the public sector to achieve their objectives efficiently, effectively, economically and ethically (4Es).